Tooth enamel hypoplasia as marker of the evolutionary stress (LLC "Endo Press", 2020)
Studying of anthropological reports of different years has shown that an enamel hypoplasia the most ancient disease of solid tissues of tooth, and the earliest data belong to an era of Neanderthal men (2-5 million years ago). Caries of teeth has been recorded at remains of people of the Neolithic era (Stone Age) when the beginning actively to develop agriculture. Features of a diet of the modern person have led to increase in occurrence of caries of enamel and reduction of not carious defects.